The role of poster as communication medium in Malaysia’s diabetic healthcare awareness / Salinatin Mohamad Saleh - Saleh, Salinatin Mohamad (2014)
Diabetes has been a prevalence disease in Malaysia. Diabetic statistic increases tremendously from 1.6 million in 2011 to 2.6 million in 2012. For many years, the government has put various efforts to educate the public on diabetes healthcare through posters. The use of poster by the government is meant to trigger the public on the hazardous alarm of diabetes. However to date, Malaysian public are still lacking of diabetic healthcare awareness. Hence, the role of diabetic healthcare poster as diabetic healthcare communication medium for the public is questionable. This study has applied a fully qualitative method to analyse public opinion on diabetic healthcare posters in five regions of Malaysia according to urban and rural area in each of the region. It has also examined the role of diabetic healthcare awareness poster towards the public. The findings from this study have revealed that the public in rural and urban area of the five regions have not fully obtained diabetic healthcare awareness despite agreeing that poster has been the only tool to communicate healthcare awareness. The rural public has more percentage on most themes and they have also got long term awareness with health behavioural change. In rural area, the availability of longer waiting time at the waiting area has also contributed towards their chances to internalize the poster to gain awareness in order to apply health behavioural change. Throughout the study, public in both regions have given opinions that they still remember the exceptional image of a rotten leg of a diabetic person from the previously unused poster. Hence, the role of poster with the use of exceptional images could construct people’s mind to gain healthcare awareness. This study has contributed beneficial entries to the Ministry of Health Malaysia in the promotion to foster a healthier lifestyle among the public besides to better understand the patterns of diabetic healthcare awareness between the urban and rural public. It also constributes towards the body of knowledge in visual communication, public health care and the field of information management.